The Effectiveness of Innovative Blended Learning Through Meaning (IBLTM) Model to Improve Students' Science Literacy - Dody Tisna Amijaya; Raharjo Raharjo; Muslimin Ibrahim; Asaduddin Al Hawari (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to determine the effectiveness of the Innovative Blended Learning Through Meaning Model (IBLTM) in improving students' scientific literacy at Muhammadiyah 2 High School Sidoarjo. Method: This study used an experimental method with a one-group pretest and posttest design. The subjects of this study were 22 students of class X-1 who participated in learning using the IBLTM Model. Data was collected through a science literacy test instrument in 12 descriptive questions covering six indicators of science literacy. Results: The results of the data analysis showed that the implementation of the IBLTM Model was effective in improving students' scientific literacy. This is indicated by a significant increase in science literacy scores from pretest to posttest, with an average N-Gain of high category. The paired t-test showed a significant difference between the pretest and posttest. In addition, all indicators of science literacy increased, with several indicators reaching the high N-Gain category. Novelty: The IBLTM model applied in this study is an innovative learning approach that integrates the process of meaning in blended learning. This model has been proven to significantly improve scientific literacy, especially in science learning at the secondary school level, and shows that an interactive and meaning-based approach can positively impact students' scientific understanding.